2013
DOI: 10.5194/bgd-10-2127-2013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Monthly measured primary and new productivities in the Ulleung Basin as a biological "hot spot" in the East/Japan Sea

Abstract: The Ulleung Basin (UB), located in the southwestern part of the East/Japan Sea (EJS), is considered having an unusually high productivity for a~deep basin. Recently changes have been reported in physical, chemical, and in biological properties. Here we measured the primary and new productivities in the UB using a <sup>13</sup>C-<sup>15</sup>N dual isotope tracer technique. Measurements took place every month for the first time throughout a year for a~better estimate of the annual… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(37 citation statements)
references
References 50 publications
2
34
1
Order By: Relevance
“…In the East Sea, the abundance of diazotrophic picocyanobacteria belonging to the genera Synechococcus and Prochlorococcus was extremely low in February and then drastically increased and peaked between late spring and autumn (Choi et al 2013;Park et al 2014). Moreover, Kwak et al (2013) reported that the contributions of picoplankton to chlorophyll a and primary production in summer were 38 ± 16 and 35 ± 2%, respectively. Therefore, our results indicate that the energy flow from the microbial loop to the top consumers may supplement the insufficient energy of the classical food web in the summer.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In the East Sea, the abundance of diazotrophic picocyanobacteria belonging to the genera Synechococcus and Prochlorococcus was extremely low in February and then drastically increased and peaked between late spring and autumn (Choi et al 2013;Park et al 2014). Moreover, Kwak et al (2013) reported that the contributions of picoplankton to chlorophyll a and primary production in summer were 38 ± 16 and 35 ± 2%, respectively. Therefore, our results indicate that the energy flow from the microbial loop to the top consumers may supplement the insufficient energy of the classical food web in the summer.…”
Section: Discussionmentioning
confidence: 93%
“…This caused a subsequent limitation in nutrient supply and the relatively low primary productivity in the surface mixed layer. Thus, during the period when stratification prevailed, cyanobacteria contributions increased at the surface layer with depleted dissolved inorganic nutrients (Kwak et al 2013). In the present study, we found an increase in the δ 13 C values of pico-to microplankton from -28.45 to -23.63‰ (Table 1).…”
Section: Discussionmentioning
confidence: 98%
“…Although nutrient concentrations in the euphotic zone (<75 m) were higher in the WSP than in the EJS, the integrated primary productivity was higher in the EJS than in the WSP [Shiomoto, 2000;Yamada et al, 2005;Kwak et al, 2013aKwak et al, , 2013b [Lozier et al, 2011]. Iron limitation may be another cause as suggested by Nishioka et al [2003] and Harrison et al [2004].…”
Section: Influence Of Hydrographic Conditions On Primary Productivitymentioning
confidence: 99%
“…For example, the vertical position of the SCM layer in relation to light and nutrient availability can control phytoplankton biomass and productivity [Martin et al, 2010]. Kwak et al [2013b] observed that the generation and destruction of the SCM layer and the associated shift in phytoplankton assemblages are related to the nature of the water column structure in the UB. Phytoplankton size and community composition directly reflect the response of phytoplankton assemblages to environmental variations [Margalef, 1978;Malone, 1980;Elser et al, 1986;Piontkovski et al, 1995;Iriarte et al, 2000].…”
Section: Introductionmentioning
confidence: 99%
“…The maintenance of high primary production in the Ulleung Basin of the JES has been explained by wind-driven coastal upwelling (Hyun et al, 2009;Yoo and Park, 2009), mesoscale eddies, which are often associated with the branch currents of the Kuroshio (Hyun et al, 2009;Kim et al, 2012;Lim et al, 2012), and hydrographic conditions (Kwak et al, 2013a). Kwak et al (2013b) measured the primary and new productivities in the UB throughout a year. The vertical structure of the water column in the basin is characterized by two distinct features: well-stratified in summer-autumn and wellmixed in winter-spring.…”
Section: Phytoplankton Responses To External Forcingmentioning
confidence: 99%